Tinjauan Kondisi Fisik Pemain Sepakbola Klub Porma Muaro Takung kabupaten Sijunjung Tahun 2020 - Yudha Ilhajri Anwar; Alnedral -; Afrizal S; Irfan Oktavianus (Performa, 2021)
Problem in research, namely the level of physical condition of the soccer players at the Porma Muaro Takung club. The purpose of this study is to determine and describe the physical condition of the Porma Muaro Takung club.The results obtained were (1) The dominant flexibility of the Porma Muaro Takung club players in Sijunjung Regency was in the medium category with an average of 14. (2) Coordination The dominant ankles owned by the Porma Muaro Takung club players, Sijunjung Regency belong to the medium category with an average 12. (3) The dominant leg muscle explosive power of the Porma Muaro Takung club player in Sijunjung Regency belongs to the medium category with an average of 152.33 cm. (4) The dominant agility of the Porma Muaro Takung club players, Sijunjung Regency, belongs to the one-time lag category with an average of 14.35 seconds. (5) The dominant speed possessed by the Porma Muaro Takung club player, Sijunjung Regency, is in the low category with an average of 4.68 seconds. (6) Dayatahn aerobics, which is dominant in the club Porma Muaro Takung, Sijunjung Regency, is in the moderate category with an average of 37.01 ml / kg.bb / min.